Anticorpos contra vírus de aves em galinhas de terreiro e cracídeos. Identificação e susceptibilidade a antimicrobianos da microbiota de cracídeos cativos no RS, Brasil. - Santos, Helton Fernandes dos (2008)
Poultry production is a very important economic activity in Brazil once the country is among the highest world avian producers. The knowledge of the pathogens epidemiology is essential to the control of infectious diseases and such control is very strict in chickens and turkeys on the avian industry. However, the avian population of the country shows a big diversity of domestic and wild birds and the chicken backyard population is out of this control. To investigate the presence of antibodies against specific viruses in the backyard chicken population, blood was collected of 867 non-vaccinated birds, from 60 farms and 22 counties from the Rio Grande do Sul State, Brazil. Neutralizing antibodies against infectious bronchitis virus (IBV) were detected in 65% (564/867) of the individuals, against avian reovirus (ARV) in 21.6% (187/867) and, against infectious bursal disease virus (IBDV) in 80.2% (695/867). The results presented on the first chapter indicated that the tested viruses are circulating among this population. Among the wild species there is a group of Galliformes, classified at the Cracidae family and commonly known as guans, chachalacas and curassows which deserved a special attention in the present study. To determine the microbiota, the bacterial resistance and the presence of antibodies against specific viruses in these birds, fifty one serum and cloacal swab samples were collected from 10 different cracid species captive in the Rio Grande do Sul State during 2007. Serum samples were submitted to serum-neutralization test and specific antibodies were detected against IBV in 5.9% (3/51) of the cracids, against ARV in 15.7% (8/51) and, against IBDV in 35.3% (18/51). All the samples were found to be negative to fowlpox virus by the AGID test. Bacterial isolation and identification were performed from the cloacal swabs. After that, the isolates were tested for antimicrobial susceptibility. Ninety three bacterial isolates were obtained from 10 different genera. Escherichia spp., Staphylococcus spp. and Streptococcus spp. are among the most prevalent genera. Antimicrobial resistance was observed in several isolates, with Serratia marcescens presenting the highest level of resistance to multi drugs followed by Streptococcus spp., Staphylococcus aureus and Escherichia coli, among others. The results from the second chapter of this dissertation allowed us to conclude that bacterial resistance is spread in the captive cracid microbiota and, most importantly, these species are susceptible to the infection by IBV, IBDV and ARV.